Mass Media Construction of Irwan Prayitno’s Leadership: A Critical Discourse Analysis - Hetti Waluati Triana; Martin Kustati; Ilham Muhammad; Reflinaldi Reflinaldi; Awliya Rahmi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
This study aims to investigate Irwan Prayitno's characters that were constructed by the mass media and the construction patterns used by each of the mass media. The study applied a descriptive model by applying mixing methods; qualitative and quantitative. The research data were obtained from Padang Ekspress, Singgalang, and Haluan print media. Following the research orientation, the data were collected from the August-November 2015 issues. Various characteristics of Irwan Prayitno’s leadership were reported with different patterns in each mass media. The differences were influenced by the practice of discourse and social practices that underlie the emergence of news. From the perspective of discourse practice, although each editor in chief emphasized the independence of media in politics, they did not deny that the owners of each media had a close relationship with certain political figures, including Irwan Prayitno. This created a high quantity of news framing the political figure. Still, the news was reported and issued following the applicable standards and procedures in the company. From a social practice perspective, information related to Irwan Prayitno was influenced by the situation and atmosphere of the West Sumatra gubernatorial election in 2015. Each of the media covered events related to Irwan Prayitno intending to capitalize on influence through reporting and advertising campaigns.